Desain Komik Etika Sosial dalam Lingkungan Budaya Masyarakat Kampung Adat Cireundeu - Rizqi, Novia Aenu; Albar, Deni (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
Cireundeu traditional village is located in South Cimahi sub-district, Cimahi City, West Java Province. The general public knows the Cireundeu traditional village because of the uniqueness of the people who still maintain cassava as a staple food, and the people who continue to carry out the Sunda Wiwitan tradition. The people of the Cireundeu traditional village are known to still uphold cultural values as the basis of life in society. These ethical values include values of decency, honesty, discipline, environmental and social care. The lack of interest of young people in learning the culture found in the Cireundeu traditional village has resulted in the loss of a regional cultural identity. Therefore, there is a need for more interesting innovations as a medium for conveying information about the culture of the Cireundeu traditional village, one of which is through comic book media. The purpose of designing this comic book is to provide information for young people about social ethical values, as well culture in the Cireundeu traditional village community. With this comic media, it is hoped that it will provide a pleasant experience in learning the culture and values that exist in the Cireundeu traditional village.